2015
DOI: 10.1128/mbio.01578-15
|View full text |Cite
|
Sign up to set email alerts
|

The Human Skin Double-Stranded DNA Virome: Topographical and Temporal Diversity, Genetic Enrichment, and Dynamic Associations with the Host Microbiome

Abstract: Viruses make up a major component of the human microbiota but are poorly understood in the skin, our primary barrier to the external environment. Viral communities have the potential to modulate states of cutaneous health and disease. Bacteriophages are known to influence the structure and function of microbial communities through predation and genetic exchange. Human viruses are associated with skin cancers and a multitude of cutaneous manifestations. Despite these important roles, little is known regarding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
232
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 236 publications
(272 citation statements)
references
References 72 publications
12
232
0
6
Order By: Relevance
“…Other viruses, such as the orthopoxvirus vaccinia virus, are cleared after epicutaneous infection. Although our current understanding of these viruses encompasses only their pathogenic behaviour, analyses of the double-stranded DNA virome have shown that papillomaviruses and poxviruses can also colonize hosts asymptomatically 21,121 . Even in the ‘simple’ case of vaccinia virus, intravital multiphoton microscopy has shown a complex spatial orchestration of immune events; although viral infection occurs in keratinocytes, responding CD8 + T cells do not target the infected keratinocytes but rather innate immune cells 122 .…”
Section: Host–pathogen Interactionsmentioning
confidence: 99%
“…Other viruses, such as the orthopoxvirus vaccinia virus, are cleared after epicutaneous infection. Although our current understanding of these viruses encompasses only their pathogenic behaviour, analyses of the double-stranded DNA virome have shown that papillomaviruses and poxviruses can also colonize hosts asymptomatically 21,121 . Even in the ‘simple’ case of vaccinia virus, intravital multiphoton microscopy has shown a complex spatial orchestration of immune events; although viral infection occurs in keratinocytes, responding CD8 + T cells do not target the infected keratinocytes but rather innate immune cells 122 .…”
Section: Host–pathogen Interactionsmentioning
confidence: 99%
“…Given this evidence of phage-host interactions and the results of recent studies illuminating the vital contributions of viruses within other human microbiota (e.g. [31,32,41]), one can surmise that phages are playing a significant role within both the bladder and reproductive system communities.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, whole metagenomic shotgun (WMS) sequencing has been employed for both taxonomic and functional annotation of skin microbial communities (Human Microbiome Project 2012b; Oh et al 2014; Hannigan et al 2015). This approach reduces amplification bias, captures multi-kingdom communities, and allows for strain-level analysis.…”
Section: Introductionmentioning
confidence: 99%